(untitled) (Revista de História da UEG (REVHIST), 2024)
Being a spatio-temporal understanding that awakens a feeling of identity in the framework of “belonging”, nationalism is an ideal that sets hearts on fire and leads crowds to recognize themselves as equals, based on the concept capable of changing the course of History, even if its origin is somehow blurred. This work, therefore, proposes to outline the structures that form the link between the co-optation of individuals under generic orders and the subsequent breaking of these paradigms with a focus on cultural specificities that, later, will organize imagined communities resulted of the same purpose, using as a point of observation a key example of such a theme: the French Revolution. Making use, especially, of the thoughts articulated by Benedict Anderson, the objectives that is up to these writings distance themselves from the laterality of abstractions already underway in the 20th century, to present the genesis of the term that displays political, cultural, sensitive facets and its direct relation with capitalism since its primitive phase, as well as directing reflections about the artificiality of the purpose that began to move crowds during the bourgeois insurrections in 18th century France. Keywords: Nationalism. French Revolution. Identity. Culture.